Microsatellite Status, Tumor Budding, CD3 and CD8 T Cell Densities in Relation to Invasiveness, Lymph Node Involvement in Colorectal Adenocarcinoma - Rebecca Noerjani Angka; Aru Wisaksosno Sudoyo; Nurjati Chairani Siregar; Wifanto Saditya Jeo; Melva Louisa; Demak Lumban Tobing (Acta Medica Indonesiana)
Background: Aside from the factors more commonly known as predictors in colorectal cancer, there are 3 additional less well-known factors, i.e., tumor budding (TB), T cell densities and loss of MMR protein expression, the aforementioned three factors are known to be independent predictive factors in CRC survival. In this study association of TB, T cell densities and loss of MMR protein were examined to see the association with differentiation, tumor location, invasiveness and lymph node invasiveness. Methods: A retrospective cohort study was conducted using 68 CRC Formalin Fixed Paraffin Embedded samples from patients who underwent removal surgeries with the diagnosis of adenocarcinoma not otherwise specified. TB counts were identified by immunohistochemical staining using Pan-Cytokeratin AE1/AE3 and were categorized into low and high. MMR protein loss was analyzed using antibodies MLH1 and MSH6 categorized as positive and negative, then classified into Microsatellite Stable (MSS) and Microsatellite Instability (MSI). CD3 and CD8 T cell densities were identified using CD3 Biocare Medical and CD8 Biocare, was categorized into low and high. Secondary data from medical records were collected and analyzed using SPSS 25. Results: A significant relationship was found between tumor budding with the depth of invasion and lymph node involvement (p=0.021 and 0.020). Conclusion: Tumor budding (TB) plays a role in the depth of invasion and lymph node involvement in CRC but has no significant relationship with CD3/CD8 densities, differentiation, location, and MMR status. There was also no significant relationship between MMR status with differentiation, location, depth of invasion, lymph node involvement, and TB.